(untitled) (The Pretoria Student Law Review, 2021)
The choice before us is not between buying or not buying organs.1 This is happening regardless of the law. The choice is whether transplant operations and the sale of organs will be regulated or not.’2 It is in light of this statement that I propose a legalised system of organ trading. Desperate people will turn to the black market regardless of the law. If organ trading could be regulated, we can protect all parties involved and ensure that they get the benefit they deserve.3 A very important factor of this way of procuring organs is that it will curb the organ shortage organ shortage. The waiting period for an organ transplant in South Africa is 5-11 years. Approximately 50% of people die while being on a waiting list for an organ transplant.4 While there is such a dire need for organs, research has shown that only 0.2% of South Africans are organ donors.5 Something must be done to motivate more people to become organ donors. While the need for organs grows daily, the black market is flourishing. As none of the organ procurement systems in other countries are successful enough to provide the need for organs, our only viable option might be to implement a payment system. When closely regulated, the system of organ trading can be an enormous success.